2021
DOI: 10.3390/children8020136
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Failure of Pneumatic Reduction in Children with Ileocolic Intussusception

Abstract: Intussusception is one of the most common causes of intestinal obstruction in children. Pneumatic reduction is the treatment of choice and has a high success rate. The most common cause of pneumatic reduction failure is the presence of a pathological leading point. We aimed to identify other factors that can lead to pneumatic reduction failure in children with ileocolic intussusception. This was a retrospective study conducted in two centers. Data were collected from January 2013 to December 2014. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It is worth noting that 90 cases (18.8%) of the enema treatments were found to be ineffective. The effectiveness of enema was found to be similar to the ndings reported by Soo-Min Jung et al [10] In cases where enema failed, surgical interventions such as intussusception reduction, enterectomy, and enterostomy were performed based on intraoperative conditions.In the present study, a cohort of 10 cases (2%) required emergency surgical intervention as part of their initial treatment, while 90 cases (18%) underwent surgery subsequent to unsuccessful enema attempts. Among the latter group, 14 cases (10%) underwent resection and enterostomy, revealing the presence of various pathological factors during the operation, including small intestine polyp, Meckel diverticulum, ectopic pancreas, and intestinal duplication.…”
Section: Discussionsupporting
confidence: 83%
“…It is worth noting that 90 cases (18.8%) of the enema treatments were found to be ineffective. The effectiveness of enema was found to be similar to the ndings reported by Soo-Min Jung et al [10] In cases where enema failed, surgical interventions such as intussusception reduction, enterectomy, and enterostomy were performed based on intraoperative conditions.In the present study, a cohort of 10 cases (2%) required emergency surgical intervention as part of their initial treatment, while 90 cases (18%) underwent surgery subsequent to unsuccessful enema attempts. Among the latter group, 14 cases (10%) underwent resection and enterostomy, revealing the presence of various pathological factors during the operation, including small intestine polyp, Meckel diverticulum, ectopic pancreas, and intestinal duplication.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies ( 1 , 3 , 35 ) found that longer duration of symptoms and bloody stool were associated with failed enema reduction, increased surgery and complications. Another meta-analysis ( 1 ) confirmed that age younger than 1 year, presence of fever and vomiting were risk factors for enema reduction failure.…”
Section: Discussionmentioning
confidence: 92%
“…Timely reduction during the obstruction of bowel blood flow is vital for rescuing strangulated intussusception and consequently minimizing eventual bowel resection 11 , 12 . Traditionally, pneumatic enema reduction at maximum pressures of 100 mm Hg has been the first-line treatment for intussusception, boasting an overall success rate of up to 90% 13 . During our pre-protocol period, the majority of patients were successfully managed through pneumatic reduction.…”
Section: Discussionmentioning
confidence: 99%